Organization of Medical Care and Drug Supply for Patients with Osteogenesis Imperfecta in the Republic of Bashkortostan - A. A. Bakirov; N. I. Romanova; V. A. Malievskiy; O. A. Malievskiy; R. Z. Akhmetshin; G. M. Galieva; E. P. Pervushina; F. M. Bairamgulov; A. K. Mardanova (Педиатрическая фармакология)
Osteogenesis imperfecta is a group of rare hereditary diseases of connective tissue, which are based on a defective collagen formation. The main focus of the osteogenesis imperfecta drug therapy is a cyclical use of bisphosphonates (pamidronic acid). The article presents the procedure of health care and drug supply organization for children with that disease, including the development of the regulatory framework.